Fear Divides, Not Unites: Volatility Transmission and Decoupling Between Cryptocurrency and Renewable Energy Markets - Al-Harbi, Ahmad (International Journal of Energy Economics and Policy, 2025)
This paper investigates the channels of price volatility transmission between speculative cryptocurrency markets and the renewable energy stock sector. We propose and test a framework of three transmission channels: (1) Energy Consumption, (2) Investment Sentiment, and (3) Policy and Regulatory. Using a two-stage GJR-GARCH and rolling correlation analysis on daily data from 2017 to 2024, with robust Newey-West standard errors to correct for autocorrelation, we uncover a nuanced relationship. After controlling for the crypto market’s correlation with the S&P 500, we find a significant negative relationship between broad market fear (the VIX) and the crypto-renewable correlation. This suggests that during periods of market panic, the assets decouple, potentially indicating a flight to quality within the risk-asset spectrum. These findings, which are robust across different time windows and pre- and post-COVID-19 subperiods, challenge simple “risk-on/risk-off” narratives. The Energy and Policy channels remain statistically insignificant, suggesting that systemic market dynamics, rather than idiosyncratic factors, are the dominant drivers of the relationship, offering critical insights for sophisticated diversification strategies.